Becoming Differently, Open Identities, and Going into the Wild - Gonzalez, Sebastian Alejandro; Sarria, Ana Mercedes (Conatus - Journal of Philosophy, 2025)
Becoming is the concept of unexpected links that are opened up by agency. Understanding that concept is, at the same time, understanding the changing possibilities expressed by those who play with reality and action based on the assumption that reality is uncontrollable. In such a way, existential experiments and reality possibilities are deeply connected scenarios. In this context, we will engage with recent debates about the concept of becoming, drawing on current interpretations of Deleuze and Guattari’s work and Thomas Nail’s contributions. In pursuing that aim, we will illustrate the idea of becoming through two concrete narrative devices: The Lover by Marguerite Duras and Into the Wild by Jon Krakauer. We follow a hermeneutical approach to identity formation processes, informed by the interdisciplinary methodological connection between text and action – i.e., the interplay between subjectivity and reflectivity in qualitative research. The central thesis is that narrated living trajectories refer to experiential scenarios associated with life experiences, disclosing reality in its diverse dimensions and possibilities. Following that consideration, we argue that becoming enables hermeneutical possibilities to comprehend open and creative enterprises.